Revealing hidden diversity and community dynamics of land snails through DNA barcoding: implications for conservation and ecological studies - Mohammadi, Sima; Ahmadzadeh, Faraham (Frontiers in Ecology and Evolution, 2024)
Land snails play a crucial role in maintaining ecosystem sustainability within their habitats. Therefore, understanding the characteristics of their communities is vital for ecological studies and the development of effective conservation strategies. In this study, we employed DNA barcoding (COI marker) to identify land snails inhabiting the Hyrcanian forest. Furthermore, we examined the variations in their community composition along elevational gradients. Snail samples were collected from three distinct elevations in three different forest locations within the Hyrcanian area of Iran. Through our comprehensive analysis, we identified a total of 10 OTUs, which were further classified into seven families and nine genera. Five of these genera had never been reported in the study region before. By employing statistical analyses such as ANOVA and PERMANOVA, we determined significant differences in the features of snail communities across different elevations. We observed a decline in OTU richness with increasing elevation; however, the maximum abundance of snails was found at higher elevations. The unique climatic conditions and spatial distribution of precipitation from lowlands to highlands, as well as from west to east, make the Hyrcanian forests an ideal case study area for understanding the dynamics of land snail communities. In summary, this study provides new insights into the land snail communities thriving in the Hyrcanian forests. The findings from our research can contribute to the development of effective conservation management strategies for forest ecosystems. By understanding the factors influencing the distribution and composition of land snail communities, we can make informed decisions to protect and preserve land snails and the balance they maintain within their habitats.